Prevalence of refractive errors in the European adult population: the Gutenberg Health Study (GHS). Issue 7 (10th February 2014) - Wolfram, Christian; Höhn, René; Kottler, Ulrike; Wild, Philipp; Blettner, Maria; Bühren, Jens; Pfeiffer, Norbert; Mirshahi, Alireza
Abstract : Objective: To study the distribution of refractive errors among adults of European descent. Design: Population-based eye study in Germany with15 010 participants aged 35–74 years. Methods: The study participants underwent a detailed ophthalmic examination according to a standardised protocol. Refractive error was determined by an automatic refraction device (Humphrey HARK 599) without cycloplegia. Definitions for the analysis were myopia <−0.5 dioptres (D), hyperopia >+0.5 D, astigmatism >0.5 cylinder D and anisometropia >1.0 D difference in the spherical equivalent between the eyes. Exclusion criterion was previous cataract or refractive surgery. Results: 13 959 subjects were eligible. Refractive errors ranged from −21.5 to +13.88 D. Myopia was present in 35.1% of this study sample, hyperopia in 31.8%, astigmatism in 32.3% and anisometropia in 13.5%. The prevalence of myopia decreased, while the prevalence of hyperopia, astigmatism and anisometropia increased with age. 3.5% of the study sample had no refractive correction for their ametropia. Conclusions: Refractive errors affect the majority of the population. The Gutenberg Health Study sample contains more myopes than other study cohorts in adult populations. Our findings do not support the hypothesis of a generally lower prevalence of myopia among adults in Europe as compared with East Asia.